Purification and Some Properties of Progenitor Toxins of Clostridium botulinum Type B - Kozaki, Shunji (1974)
Purification of progenitor toxin of Clostridium botulinum type B strain Okra was undertaken by sequential steps of acid precipitation, extraction, ammonium sulfate precipitation, ribonuclease digestion, acid precipitation, protamine treatment, sulphopropyl-Sephadex chromatography, and Sephadex G-200 gel filtration. Two different molecular-sized toxins, named large (L) and medium (M) toxins, were obtained. L toxin was centrifugally homogeneous but electrophoretically heterogeneous. It contained 2.5 × 10(8) to 3.0 × 10(8) mean lethal doses per mg of nitrogen, and its sedimentation constant was 16S. M toxin was centrifugally and electrophoretically homogeneous. It contained 5.5 × 10(8) to 6.0 × 10(8) mean lethal doses per mg of nitrogen, and its sedimentation constant was 12S. The presence of both L and M toxins in spent culture was demonstrated. It seems justified, therefore, to call both progenitor toxins. Both consisted of toxic and nontoxic components. The toxic components of L and M toxins appeared to be identical with each other. The nontoxic component of L toxin was 12S and possessed a hemagglutinin activity of about 0.5% that of type A crystalline toxin; that of M toxin was 7S and possessed no hemagglutinin activity. They were antigenically related but not identical.